2011
DOI: 10.1093/molbev/msr063
|View full text |Cite
|
Sign up to set email alerts
|

Numerous Fragmented Spliceosomal Introns, AT-AC Splicing, and an Unusual Dynein Gene Expression Pathway in Giardia lamblia

Abstract: Spliceosomal introns are hallmarks of eukaryotic genomes, dividing coding regions into separate exons, which are joined during mRNA intron removal catalyzed by the spliceosome. With few known exceptions, spliceosomal introns are cis-spliced, that is, removed from one contiguous pre-mRNA transcript. The protistan intestinal parasite Giardia lamblia exhibits one of the most reduced eukaryotic genomes known, with short intergenic regions and only four known spliceosomal introns. Our genome-wide search for additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…S2A). Furthermore, it has been revealed that RNA base-pairing is critical for the trans-splicing (Fischer et al 2008;Kamikawa et al 2011;Roy et al 2011). We assembled each set of the 59 and 39 trans-introns to reveal potential RNA base-pairings.…”
Section: Identification Of Trans-splicing Events In the Silkwormmentioning
confidence: 99%
“…S2A). Furthermore, it has been revealed that RNA base-pairing is critical for the trans-splicing (Fischer et al 2008;Kamikawa et al 2011;Roy et al 2011). We assembled each set of the 59 and 39 trans-introns to reveal potential RNA base-pairings.…”
Section: Identification Of Trans-splicing Events In the Silkwormmentioning
confidence: 99%
“…1D); and (iii) the recently-discovered G. lamblia cleavage motif (with consensus TCCTTTACTCAA; Fig. 1D; Hudson et al, 2012). A BLASTX search of the mature trans-spliced transcript against Genbank revealed homology to p68 helicase (Fig.…”
Section: A Trans-spliced Intron In a P68 Helicase Genementioning
confidence: 93%
“…Recently, the first case in which a substantial fraction of introns in an organism are trans-spliced was reported. In the genome of the diplomonad intestinal parasite G. lamblia, systematic studies have revealed only six cis-spliced introns to date (Nixon et al, 2002;Russell et al, 2005;Morrison et al, 2007;Roy et al, 2012;Franzén et al, 2013); intriguingly small-scale studies revealed four cases of genic trans-splicing, including two in a single gene (Nageshan et al, 2011;Kamikawa et al, 2011;Roy et al, 2012;Hudson et al, 2015). These cases showed distinctive sequence featuresmost notably extended basepairing potential between the pairs of trans-spliced transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, it was believed that G. intestinalis possesses neither a typical mitochondrion with respiratory function nor spliceosomal introns (Adam 2000). We now know that G. intestinalis secondarily lost its mitochondria (Roger et al 1998;Hashimoto et al 1998;Tovar et al 2003), and five genes had been found to bear canonical (cis-spliced) spliceosomal introns in its genome (Nixon et al 2002;Morrison et al 2007;Roy et al 2011). These findings suggest that this organism does not necessarily represent the ancestral eukaryotes; rather, they lost the typical mitochondria because of their anaerobic lifestyle, and spliceosomal introns in the G. intestinalis genome are merely more sparse than those in other eukaryotic genomes.…”
Section: Introductionmentioning
confidence: 99%